Taxes and the location of production - Lynda Porter (University College Dublin, Department of Economics, 2003)
In this paper I examine dynamic tax competition in the context of an endogenous market structure. I therefore consider the tensions between proximity versus concentration, taxation and firm mobility while I also consider strategic interaction by governments (to induce multinationality) and asymmetric firms (for market share). The paper explores how strategic tax setting by rival governments may induce footloose firms to remain committed to initial location decisions, even when faced with adverse taxation regimes. In this instance, sunk costs resulting from the operation of additional plants may confer a first mover advantage on governments that can prevent relocation of firms.
hdl:10197/1790
Keywords: 330; Steuerwettbewerb; Betriebliche Standortwahl; Unvollkommener Wettbewerb; Theorie; Wiederholte Spiele